Technology Design for Controlling Cultivation Contamination in Erhai Basin Based on the Theory of Recycling Economy - Yiqiong, Cao; Qian, Xu; Limin, Dong (Energy procedia, 2011)
The pollution situation of which is going to analyzed later, the water resource in Erhai Basin is chosen to be the subject of this research by presenting the technology called the solar medium heat steel form solid-liquid joint fermentation biogas technology, which is based on 3R principle. The aim of this research is to do further improvement in recyclable use of resource, reducible discharge of waste water and also realization of win-win cooperation of society, economy and ecological environment in certain area.